Affective decision-making - Russell-Bennett, Rebekah (Henry Stewart Talks, 2013)
Types of consumer decisions, Unconscious decisions, Emotion based decisions, Habitual decisions, Primary and secondary emotions, Affective events theory, Affect infusion model, Affect as information, Emotions as social information, Marketing desire, Affective forecasting, Anticipated regret, sadness and happiness, Emotions and advertising, The use of fear